MANAJEMEN KOMPETENSI GURU PAI DALAM PEMBENTUKAN AKHLAKUL KARIMAH SISWA - Muaddyl Akhyar; Martin Kustati; Rezki Amelia; Aisyah Syafitri (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
Competency management of PAI teachers is not only related to theoretical understanding of religion, but also their ability to deliver subject matter in an interesting way, motivate students to apply religious values in their lives, and create a learning environment that supports students' moral development in shaping students' morals. The purpose of this study is to explain the Competency Management of PAI Teachers in the Formation of Moral Character of Students of SMPN 2 Sintoga Padang Pariaman. The method used in this study uses a qualitative method with a case study approach. The case study approach is a powerful tool for exploring a particular situation or event carefully, deeply, and in detail. This approach allows researchers to gain a better understanding of the complexity and dynamics of a phenomenon or problem in a real context. The results of this study show that the role of PAI teachers, the initiatives and teaching methods used, as well as the positive impacts, we can appreciate the school's efforts in shaping better student characters. However, challenges and measures of success must also be considered so that PAI teachers' competency management can continue to improve and contribute to students' educational and moral development in the future. PAI teachers' competency management plays a key role in shaping students' good character. With a strong commitment, schools can continuously improve this process and make a significant positive contribution to students' religious education and moral development in the future. Abstrak Manajemen kompetensi guru PAI tidak hanya berkaitan dengan pemahaman teoritis agama, tetapi juga kemampuan mereka dalam menyampaikan materi pelajaran dengan cara yang menarik, memotivasi siswa untuk menerapkan nilai-nilai agama dalam kehidupan mereka, dan menciptakan lingkungan belajar yang mendukung perkembangan moral siswa dalam membentuk akhlakul karimah siswa. Tujuan penelitian ini menjelaskan tentang Manajemen Kompetensi Guru PAI dalam Pembentukan Akhlakul Karimah Siswa SMPN 2 Sintoga Padang Pariaman. Metode yang digunakan dalam kajian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Pendekatan studi kasus adalah alat yang kuat untuk menjelajahi situasi atau peristiwa tertentu dengan cermat, mendalam, dan rinci. Pendekatan ini memungkinkan peneliti untuk mendapatkan pemahaman yang lebih baik tentang kompleksitas dan dinamika suatu fenomena atau masalah dalam konteks nyata. Hasil penelitian ini menunjukkan bahwa adanya peran guru PAI, inisiatif dan metode pengajaran yang digunakan, serta dampak positifnya dalam pembentukan akhlak siswa. Dengan komitmen yang kuat, sekolah dapat terus meningkatkan proses ini dan memberikan kontribusi positif yang signifikan pada pendidikan agama dan pembentukan akhlakul karimah siswa di masa depan.